DETERMINING PRIORITY METHODS FOR COMBATING SOCIAL INEQUALITY IN SCHOOLS: CREATING A SAFE ENVIRONMENT FOR SCHOOLCHILDREN - Kryshtanovych, Svitlana (Socio-economic relations in the digital society, 2025)
It should be noted that the problem of social inequality in schools is becoming particularly relevant today since education is considered a key component of the formation of human capital. In our opinion, ensuring a safe environment in school cannot be effective without taking into account various manifestations of discrimination and bullying, as well as without proper psychological support for students from socially vulnerable categories. As part of this study, we identified six potential methods for combating social inequality (in particular, in-depth programs for the development of empathy and tolerance, the introduction of an "equality code", strengthening psychological services, and others). The results were obtained with the involvement of 40 experts (school principals, experienced teachers, psychologists, social workers and safety specialists) who participated in a two-stage survey using the Delphi method. The second stage of the analysis used the Analytical Hierarchy Process (AHP) method, which allowed for pairwise comparisons of criteria (effectiveness in reducing bullying and discrimination, impact on psycho-emotional state, economic feasibility, institutional support) and alternatives. It should be emphasized that the obtained quantitative data make it possible to assess the relative priority of each method taking into account the agreed expert assessments. The highest integral weights were given to measures to expand psychological support for students, the "equality code" and financial assistance for vulnerable families, which indicates the need to combine both psycho-emotional and material-institutional instruments. It can be argued that such results have significant applied potential since a comprehensive approach to combating social inequality can be integrated into school curricula, regulatory documents and educational development strategies at the state and local levels. In our opinion, further research should focus on developing step-by-step methodological recommendations and monitoring the implementation of the described tools in different types of schools.
Keywords: social inequality; safe environment; school; Analytical Hierarchy Process (AHP); Delphi Method; bullying; psychological support